TINJAUAN HUKUM JUAL BELI HANDPHONE (HP) BEKAS DALAM PERSPEKTIF ISLAM (STUDI KASUS UD. VIRGO CELL ROGOJAMPI - Yeny Rokhilawati; Habibulloh Habibulloh; Ridhwan Nasrulloh (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2023)
This study aims to explain the law of buying and selling used cellphones (Hp) in an Islamic perspective (UD case study. Virgo Cell Rogojampi). This research uses a qualitative descriptive approach. In the data collection process, it uses several methods, namely observation, interviews, and documentation. Data analysis techniques use qualitative data analysis (data reduction, data presentation and drawing conclusions). as for the results of the research that buying and selling mobile phones at UD Virgo Cell Rogojampi uses a murabahah contract and the law of buying and selling is in accordance with islamic perspectives